PERAN AJARAN TASAWUF SEBAGAI PSIKOTERAPI MENGATASI KONFLIK BATIN - Waslah Waslah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2017)
Amid the crises of life which is too materialistic, secular as well as a very hard life, economically and psychologically, Sufism provides the antidote spiritual, which gives resilience to the crisis of spirituality modern which has resulted in them no longer know who he is meaning and purpose of life on earth. The lack of clarity on the meaning and purpose of life, eventually resulted in a prolonged agony. The purpose of this study to determine the type - the type of inner conflict can be resolved with psychotherapy mysticism, Sufism as describe the role of psychotherapy in overcoming inner conflicts, and to describe the implementation of Sufism as psychotherapy in overcoming inner conflicts. This research includes the study of literature and when viewed in terms of closers including qualitative research because the data presented in the form of a statement-pernyataan.Untuk answer psychological problems, Sufism teaches about a happy life. Happy life should be alive and well both physically and mentally. Live happily with the inner conflict will never be obtained. This is because the happiness that is created will throw the whole mind - pikran inner nature